Resistance to Lutheran missionary activities through antagonism, traditional beliefs, customs and practices: The case of the Bapedi tribe in Limpopo province, South Africa - Lebaka, Morakeng E. K. (HTS teologiese studies, 2020)
Before the intervention of the missionaries in Bapedi society, the traditional beliefs, customs and practices, such as traditional healing, circumcision, polygamy, indigenous music and rituals, had a vibrant existence. These practices had been prevalent for centuries before the arrival of Christianity. After the missionaries of all church denominations were welcomed in Bapedi society to establish churches and schools as the main vehicles for the dissemination of European culture, confusion started to build. In this article, I will highlight the reaction of Bapedi people of Sekhukhune district, Limpopo province, South Africa, to the missionary activities of Berlin Mission Society (BMS), Germany, from 19 July 1860 to 08 July 2018. The purpose of this study was to explain the conflict or integration of different cultural norms and the missionary influence on the Bapedi indigenous way of life. The questions that I attempt to answer in this article are: (1) how do people understand one another when they do not share a common cultural experience? and (2) who are to blame, the missionaries or the Bapedi people themselves? I address this question by analysing the missionary influence on Bapedi traditional beliefs, customs and practices. Primary data were collected through video recordings of cultural and religious rituals, interviews and observations. Secondary data include publications. It was concluded that in spite of fundamental and multi-consequential changes that Christianity brought about in Bapedi society, a large percentage of Bapedi people, independent churches inclusive, have used and are still following their traditional beliefs, taboos, customs and practices.